Pengaruh Remunerasi, Pengalaman Kerja dan Budaya Kerja terhadap Komitmen Organisasional serta Implikasinya terhadap Kinerja Pegawai (Survey pada Pegawai BPS Provinsi Sumatera Utara) - Subadrianto, Al Sufi; Priadana, Sidik; Julius, Horas (Future Science, 2024)
The Influence of Remuneration, Work Experience and Work Culture on Organizational Commitment and Its Implications for Employee Performance (Survey of BPS Employees in North Sumatra Province). The quality of public services in providing data and information at the North Sumatra Province level will greatly depend on the ability of North Sumatra Province BPS employees to provide services that are reflected in the performance of their employees. . Increasing employee performance in the field of community service will have an impact on increasing public trust in BPS in North Sumatra Province. This research aims to determine and examine remuneration, work experience and work culture on organizational commitment and its implications for the performance of BPS employees in North Sumatra Province. This research uses a quantitative approach with descriptive and verification analysis. In this study, the sample members were 273 employees at BPS North Sumatra Province. The analytical method in this research uses SEM (Structural Equation Model) analysis. The research results concluded that there is a significant influence of Remuneration, Work Experience and Work Culture on Organizational Commitment with an influence size of 72.37 percent, and there is a significant influence. from Organizational Commitment to employee performance with an influence size of 80.77 percent